(untitled) (مجلة إحالات, 2026)
This research paper focuses on the components of national identity and their concepts according to Abdelhamid Ben Badis. He viewed identity as a set of stable, diverse connections and sought to restore the Algerian nation by reviving its character through various reforms. Ben Badis was a reformer and a leader in the Algerian struggle against French colonialism, which aimed to erase Algerian national identity. This paper will outline the national components of the Algerian people as defined by Ben Badis, including Islam, the Arabic language, and the homeland, along with his reformist and activist journey to defend these elements and inspire the Algerian people to reclaim their sovereignty and identity.